Wokół problemu definicji mniejszości narodowych - Sobczak, Jacek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2003)
The problem of national minorities appears to be quite a controversial issue. This is so because it is considered by lawyers, sociologists, culture researchers, historians and political scientists. It is not a trivial matter in the controversies caused by this problem that it is related to a particularly sensitive political area that in political practice generates immense problems and brings about conflicts. The paper attempts to group the definitions developed by sociology and political science and to demonstrate the most controversial elements. The problem of national minorities is related to the notions of nation, nationality, ethnic minority and ethnographic minority. The main emphasis falls on the legal approach as the attempts at developing a legal definition (i.e. the definition stipulated by the act of law) are traced while acknowledging that such a definition has not been developed although numerous acts of international law concern the issues of minorities.